2014
DOI: 10.3748/wjg.v20.i21.6573
|View full text |Cite
|
Sign up to set email alerts
|

Role of cystatin C and renal resistive index in assessment of renal function in patients with liver cirrhosis

Abstract: Cystatin C may be a more reliable marker for assessment of liver insufficiency. Additionally, cystatin C and renal resistive index represent sensitive indicators of renal dysfunction in patients with liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
5
13
0
1
Order By: Relevance
“…Comparison of CysC among Child–Pugh stages and correlation with a MELD score showed statistically significant results, which were presented earlier in our article [16]. …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Comparison of CysC among Child–Pugh stages and correlation with a MELD score showed statistically significant results, which were presented earlier in our article [16]. …”
Section: Resultssupporting
confidence: 84%
“…Basic demographic data of our patients were presented earlier [ 16 ] ( Table 1 ). The average diameter of the portal vein, HARI and CysC were significantly larger in the study group, while blood flow velocity was significantly slower ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, nephrologists and clinical laboratory experts are being engaged in the exploration of the relationship between serum CysC and secondary kidney impairment in hepatic cirrhosis patients, [ 21 23 ] especially in those with normal SCr. [ 24 ] Available studies suggest that, as compared with SCr, serum CysC in a certain extent may be a more sensitive marker for assessment of kidney impairment in patients with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported its value in different sets of patients [ 9 16 ]. However, only few studies have evaluated the role of serum CysC in patients with liver cirrhosis [ 17 – 19 ] and none of these studies have studied its role in detecting early renal impairment in these patients. In our study, we aimed at evaluating the role of serum CysC as a marker of the renal function in patients with liver cirrhosis and, more important, as an indicator of renal impairment at its early stages in such patients.…”
Section: Introductionmentioning
confidence: 99%